2009
DOI: 10.1007/s10295-009-0604-1
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium acetate enhances solvent production by Clostridium acetobutylicum EA 2018 using cassava as a fermentation medium

Abstract: Cassava, due to its high starch content and low cost, is a promising candidate substrate for large-scale fermentation processes aimed at producing the solvents acetone, butanol and ethanol (ABE). However, the solvent yield from the fermentation of cassava reaches only 60% of that achieved by fermenting corn. We have found that the addition of ammonium acetate (CH(3)COONH(4)) to the cassava medium significantly promotes solvent production from cassava fermented by Clostridium acetobutylicum EA 2018, a mutant wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 27 publications
(23 reference statements)
1
32
0
Order By: Relevance
“…Most nitrogen sources of protein exist as a powder or paste material; if added to the fermentation medium, this kind of nitrogen source increases the viscosity and leads to difficulties for adjusting the pH. 28 Therefore, inorganic ammonium acetate was selected for use in this study.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Most nitrogen sources of protein exist as a powder or paste material; if added to the fermentation medium, this kind of nitrogen source increases the viscosity and leads to difficulties for adjusting the pH. 28 Therefore, inorganic ammonium acetate was selected for use in this study.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Gu et al (2009) found an increase in the solvent productivity by C. acetobutylicum with the addition of ammonium acetate using cassava medium. Continuous fermentations have an advantage of a shorter downtime, automatic operation tends to be simpler and usually they exhibit higher productivity than in batch fermentations (Jin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…To increase yield and productivity, fermentation broth additives such as acetate (6,7) and calcium carbonate (3,8,9) have been successfully utilized. During ABE fermentation by solventogenic Clostridium species, CaCO 3 has been shown to stimulate sugar utilization, butanol production, and butanol tolerance (3,8,9).…”
mentioning
confidence: 99%